2013
DOI: 10.1002/glia.22549
|View full text |Cite
|
Sign up to set email alerts
|

Retinal regeneration in adult zebrafish requires regulation of TGFβ signaling

Abstract: Müller glia are the resident radial glia in the vertebrate retina. The response of mammalian Müller glia to retinal damage often results in a glial scar and no functional replacement of lost neurons. Adult zebrafish Müller glia, in contrast, are considered tissue-specific stem cells that can self-renew and generate neurogenic progenitors to regenerate all retinal neurons after damage. Here, we demonstrate that regulation of TGFβ signaling by the corepressors Tgif1 and Six3b is critical for the proliferative re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
120
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(125 citation statements)
references
References 57 publications
4
120
0
1
Order By: Relevance
“…If instead Müller glia dedifferentiated completely and were transformed into neuroepithelial cells, then defects in lamination would result, as observed when Müller glia are eliminated by the gliotoxin DL-α-aminoadipic acid (Rich et al, 1995). Second, it explains why the planimetric density of Müller glia is unchanged after regeneration is completed (this study) (Lenkowski et al, 2013). Third, it provides an explanation for why retinal injury in fish does not provoke reactive gliosis and formation of a 'glial scar' characteristic of retinal lesions in mammals (Bringmann et al, 2006;Karl and Reh, 2010).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…If instead Müller glia dedifferentiated completely and were transformed into neuroepithelial cells, then defects in lamination would result, as observed when Müller glia are eliminated by the gliotoxin DL-α-aminoadipic acid (Rich et al, 1995). Second, it explains why the planimetric density of Müller glia is unchanged after regeneration is completed (this study) (Lenkowski et al, 2013). Third, it provides an explanation for why retinal injury in fish does not provoke reactive gliosis and formation of a 'glial scar' characteristic of retinal lesions in mammals (Bringmann et al, 2006;Karl and Reh, 2010).…”
Section: Discussionmentioning
confidence: 80%
“…The importance of cell-cell adhesion and directed cell migration in retinal regeneration has received scant attention, and instead the focus has been on examining transcriptional networks and secreted signals that promote Müller-dependent retinal neurogenesis (Karl and Reh, 2010;Fischer and Bongini, 2010;Thummel et al, 2010;Ramachandran et al, 2010b;Ramachandran et al, 2011;Wan et al, 2012;Nelson et al, 2012;Lenkowski et al, 2013). We showed previously that cells in the neurogenic clusters strongly upregulate both N-cadherin and Notch components , and recent studies demonstrate a functional role for Notch signaling along with secreted heparin-binding epidermal growth factor (HB-EGF) and Wnt/β-catenin, which cooperatively modulate a regulatory network activated during retinal regeneration targeting the neurogenic transcription factors Pax6b and Ascl1a (Ramachandran et al, 2011;Wan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies on ex vivo cultured rat retinae, an inhibitory effect of TGF-β signaling on the proliferation of postnatal progenitors and Müller glia was shown (Close et al 2005). Lenkowski and coworkers demonstrated that TGF-β signaling inhibits proliferation of neuronal progenitor cells in a zebrafish model of retinal regeneration (Lenkowski et al 2013). Moreover, there is experimental evidence that TGF-β signaling is a negative modulator of adult neurogenesis in the rodent brain (Wachs et al 2006) and that high TGF-β1 levels keep adult stem cells quiescent in the hippocampus (Wachs et al 2006;Kandasamy et al 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Activation of GCR appears to directly inhibit FGF2/MAPK signaling and the initiation of Müller glial de-differentiation in undamaged retinas, whereas Müller glia in NMDA-damaged retinas appear to be influenced by many signaling pathways in addition to GCR and MAPK. These pathways probably include Wnt/β-catenin (Osakada et al, 2007;Ramachandran et al, 2011), Jak/Stat3 (Nelson et al, 2012), TGFβ/Smad (Close et al, 2005;Lenkowski et al, 2013) and TNFα (Nelson et al, 2013). Any one of these pathways in the damaged retina could influence Notch signaling independently of MAPK and GCR signaling.…”
Section: Discussionmentioning
confidence: 99%